Acoustic features of labial and dental plosives in children with hypernasality - Tosun, Samet; Karsan, Çağdaş (Revista de Investigación en Logopedia, 2024)
Cleft lip and palate (CLP) is a birth defect that can have negative effects on feeding, physical appearance, speech, hearing, and psychological development.VFI-induced hypernasality are high-pressure sounds such as plosives, fricatives, and affricates. In this study, the influence of hypernasality on plosive sounds was investigated. Six children with CLP with hypernasality and six children with typical development participated in this descriptive comparative study. All of the participants were between 10 and 12 years old and were native Turkish speakers. These two groups were matched by age and gender. For the acoustic analysis, the stop component, burst duration, and total duration of each target sound were calculated. Additionally, voice onset time (VOT) was assessed and contrasted between groups. A linear mixed-effects model was used for the statistical analysis. This study demonstrates that children with hypernasality have longer target sound durations. In addition, the burst duration of target sounds is determined to be prolonged in this group. Moreover, hypernasality is linked to a prolonged stop duration. Children without hypernasality experience a shortened duration of VOT than those with hypernasality. According to this study's findings, velofarengeal insufficiency has an effect on the duration of obstruent sounds. This explains the differences between the hypernasality group and the non-hypernasality group. This research suggests that CLP therapy for children may enhance their condition. Using acoustic measurements, this investigation generates theoretical results. Therapies' administration and evaluation could be combined.
Keywords: hypernasality; cleft lip palate; front plosive sounds; VOT